THE EFFICIENCY OF ZAKAT COLLECTION AND DISTRIBUTION: EVIDENCE FROM DATA ENVELOPMENT ANALYSIS - Ninda Ardiani (Universitas Negeri Surabaya, 2019)
The purpose of this study is to see the efficiency of the national zakat institutions in the collection of funds and distribution. Dompet Dhuafa is one of the national zakat institutions which has branch office spread in Indonesia. The problem is how efficient is the institution of zakat when collecting zakat funds and channeling it. This research uses Data Envelopment Analysis (DEA) method with two test that is test for zakat fund and test to non-zakat fund. Input variables consist of receipts obtained by zakat institutions, while the output variables consist of expenditures for 8 asnaf and other expenditures. Data taken from Dompet Dhuafa financial statements from 2011 to 2015. The results of this study addressed in 2011, 2014 and 2015 Dompet Dhuafa in collecting and disbursing zakat funds and non-zakat funds have been efficient. Inefficiencies that occur in the year 2012 and 2013 due to not optimal channeling of funds from Dompet Dhuafa.